2006
DOI: 10.1021/jp0654462
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of IR Luminescence of Erbium, Neodymium, and Ytterbium β-Diketonate Complexes by Ligand C−H and C−D Bonds

Abstract: The effect of CH and CD quenching on the luminescence lifetime of Er(3+) Nd(3+) and Yb(3+) in the Cs[Ln(HFA)(4)] system has been quantified, and we have shown that for Er(3+) ions the quenching is dominated by the nearest neighbor CH oscillators, whereas for Nd(3+) ions the roles of more distant CH oscillators and nearest neighbor CD oscillators are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 11 publications
6
87
0
Order By: Relevance
“…5 We recently quantified the role of CH oscillators in the quenching of erbium by deuterating the ͓Cs͔͓Er͑HFA͒ 4 ͔ ͑H-HFA is 1,1,1,5,5,5-hexafluoro-2,4-pentanedione͒ system, which has only one C-H bond per ligand, and we showed that any hydrogen within 20 Å of an erbium ion acts as an efficient quenching center. 6,7 Mancino et al 8 have shown that an evaporated thin film of Er͑F-tpip͒ 3 , where F-tpip is perfluorinated imidodiphosphinate ͓͑C 6 F 5 ͒ 2 P͑O͔͒ 2 N − , has a luminescence lifetime of 224 s and this system, with no hydrogen, has a lifetime still considerably shorter than that expected for isolated ions. We have recently investigated the perfluorinated diphenylphosphinate system Er͓͑C 6 F 5 ͒ 2 PO 2 ͔ 3 , 9 which forms a thermally stable but highly insoluble coordination polymer, and found that in the as-grown state, we can obtain luminescence lifetimes of ϳ0.5 ms. Again, this is still significantly worse than might be expected from isolated ions and suggests that other quenching mechanisms are operating.…”
mentioning
confidence: 99%
“…5 We recently quantified the role of CH oscillators in the quenching of erbium by deuterating the ͓Cs͔͓Er͑HFA͒ 4 ͔ ͑H-HFA is 1,1,1,5,5,5-hexafluoro-2,4-pentanedione͒ system, which has only one C-H bond per ligand, and we showed that any hydrogen within 20 Å of an erbium ion acts as an efficient quenching center. 6,7 Mancino et al 8 have shown that an evaporated thin film of Er͑F-tpip͒ 3 , where F-tpip is perfluorinated imidodiphosphinate ͓͑C 6 F 5 ͒ 2 P͑O͔͒ 2 N − , has a luminescence lifetime of 224 s and this system, with no hydrogen, has a lifetime still considerably shorter than that expected for isolated ions. We have recently investigated the perfluorinated diphenylphosphinate system Er͓͑C 6 F 5 ͒ 2 PO 2 ͔ 3 , 9 which forms a thermally stable but highly insoluble coordination polymer, and found that in the as-grown state, we can obtain luminescence lifetimes of ϳ0.5 ms. Again, this is still significantly worse than might be expected from isolated ions and suggests that other quenching mechanisms are operating.…”
mentioning
confidence: 99%
“…[ 7 ] The main reason for the low UC effi ciency in organic compounds containing trivalent lanthanides is the strong nonradiative quenching of the lanthanide excitation by the O-H, C-H, and N-H units usually present in these systems. [ 12 ] Multiphonon relaxation of the excited states due to their interaction with the high energy oscillators [ 13 ] associated with these groups competes with and overwhelms the possibility of energy transfer and other radiative processes. Thus, the overall effi ciency is greatly reduced and so is the applicability of the organolanthanides for UC.…”
Section: Doi: 101002/adma201002674mentioning
confidence: 99%
“…From recent work on deuterated Cs[Er(HFA) 4 ] [7], it has been demonstrated that any C-H oscillators within 20 Å of an erbium ion can quench the lifetime to <100 µs, so the low levels of solvent detected in these samples would be sufficient to limit the lifetime to the observed value of 20.2 µs. Compared with the 1.8 µs lifetime observed for Cs[Er(HFA) 4 ], where the hexafluoroacetylacetonate (HFA) ligands each contain a single C-H bond, there is a considerable extension in lifetime associated with exclusion of hydrogen from the environs of the erbium ion.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…However, full deuteration of ligands is rarely achieved and the presence of any 1 H within 20 Å of an Er 3+ ion can be lifetime-limiting [7]. The use of fluorinated ligands such as (C 8 F 17 SO 2 ) 2 N -and [(C 6 F 5 ) 2 PO] 2 N -is another option [8,9].…”
Section: Introductionmentioning
confidence: 99%